Android-based high school physical learning model - Mariati, Sari; Warti, Yani; Sari, Suci Nanda; Sari, Desi Purnama (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: This research is based on the limited teaching and learning activities of physical education in schools, because the current pandemic situation still limits student learning activities in schools. Purpose: This research aims to produce a learning product for students as well as in the form of materials/textbooks and an android application that contains physical education materials to create more effective and efficient learning. Methods: The type of research method used in this study is research and development using the ADDIE Model. Results: This android-based PJOK learning model in the initial trial stage got a practicality percentage of 80% with the category